(untitled) (Studia Prawnicze / The Legal Studies, 1975)
Administracja polska jest administracją typu socjalistycznego. Organizacja administracji państwowej w każdym kraju nie jest i nie może być kształtowana dowolnie. Jest uzależniona od szerszej kategorii tj. organizacji aparatu państwowego. Jest rezultatem oddziaływania całego szeregu przesłanek: politycznych, historycznych, geograficznych, gospodarczych, demograficznych, kulturowych i wielu innych. Autor artykułu zapoznaje nas z pojęciem kierowania w nauce administracji, wskazując na prawne ujęcie opisanych zależności. Ponadto przedstawia teorie prawa administracyjnego zarówno socjalistyczną jak i zachodnią. Ponadto w artykule przedstawione problemy związane są z kierownictwem organizacyjnym w administracji. The Polish administration is a socialist type of administration. The organisation of the state administration in any country is not and cannot be shaped arbitrarily. It depends on a broader category, i.e. the organisation of the state apparatus. It results from the interaction of a whole range of considerations: political, historical, geographical, economic, demographic, cultural and many others. The author of the article introduces us to the concept of management in the science of administration, pointing out the legal treatment of the relationships described. In addition, he presents both socialist and western administrative law theories. In addition, the problems presented in the article are related to organisational leadership in administration.